Phasic left atrial strain to predict diastolic dysfunction development in women: results from the prospective Berlin Female Risk Evaluation (BEFRI) follow up trial. (4th February 2022) - Brand, A; Romero Dorta, E; Blaschke-Waluga, D; Wolf, A; Stangl, K; Seeland, U; Regitz-Zagrosek, V; Knebel, F; Dreger, H; Stangl, V
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Supported by the DZHK (German Centre for Cardiovascular Research) and by the BMBF (German Ministry of Education and Research) OnBehalf: BEFRI Background/Introduction: During the past few years, left atrial strain (LAS) has been identified to be significantly associated with left ventricular diastolic dysfunction (DD). However, the predictive value of LAS reductions on the course of DD in patients without or mild DD has so far not been investigated. Purpose: To assess the predictive impact of phasic left atrial strain (LAS) reductions on the development of left ventricular (LV) diastolic function in women with normal (DD0) or mildly impaired diastolic function in a longitudinal study design. Methods: We reinvited 449 participants of the Berlin Female Risk Evaluation (BEFRI) study for follow-up examinations. A comprehensive clinical and echocardiographic assessment comprising the analysis of phasic LAS was performed in 256 participants. The diagnostic and predictive value of LAS analysis was assessed and compared with standard echocardiographic DD parameters using receiver operating characteristic (ROC) curve analyses and a multivariate logistic regression model. Results: After a mean time interval of 6.8 years, subjects with DD0 at baseline investigation and a worsening of diastolic function of at least one stage according to recent ASE / EACVI recommendations (DD_progress) showed a significantly reduced baseline LA reservoir strain (LASr) and conduit strain (LAScd) [LASr 28.1% (6.9) in DD_progress vs. 41.9% (8.5) in DD0 at follow up; and LAScd -13.2% (5.0) in DD_progress vs. -25.4% (9.1) in DD0 at follow up; p < 0.001 respectively]. With an area under the curve (AUC) of 0.89 [95% confidence interval (CI) 0.83-0.94], and 0.85 (95% CI 0.80-0.90), LASr and LAScd showed the highest discriminative value to predict DD_progress while the echocardiographic standard DD parameter left atrial volume index (LAVI) featured a limited predictive diagnostic accuracy [AUC of 0.65 (95%CI 0.52-0.72)]. In a multivariate logistic regression model controlling for age, BMI, and other standard echocardiographic DD parameters including LAVI, only LASr and LAScd remained significantly associated with DD_progress over time. Conclusions: In addition to improving the diagnostic accuracy of the current DD algorithm, the analysis of phasic LAS reductions may be useful to predict the development of DD in previously healthy women.